2016
DOI: 10.1016/j.molcel.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Sulfenylation Directs IRE-1 to Activate the SKN-1/Nrf2 Antioxidant Response

Abstract: SUMMARY Emerging evidence suggests that many proteins may be regulated through cysteine modification, but the extent and functions of this signaling remain largely unclear. The endoplasmic reticulum (ER) transmembrane protein IRE-1 maintains ER homeostasis by initiating the unfolded protein response (UPRER). Here we show in C. elegans and mammalian cells that IRE-1 has a distinct redox-regulated function in cytoplasmic homeostasis. Reactive oxygen species (ROS) that are generated at the ER or by mitochondria s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
211
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(221 citation statements)
references
References 74 publications
10
211
0
Order By: Relevance
“…The beneficial effects of low-dose mitochondrial ROS on healthspan and lifespan arise from a hormetic adaptation to mild stress (Hekimi et al, 2011; Shadel, 2014; Ristow and Schmeisser, 2014). Similarly, it was shown recently that ROS production arising from perturbed ER redox homeostasis leads to a protective response that increases lifespan (Hourihan et al, 2016). In each of these examples, mutants that lack the capacity to detoxify ROS (e.g.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The beneficial effects of low-dose mitochondrial ROS on healthspan and lifespan arise from a hormetic adaptation to mild stress (Hekimi et al, 2011; Shadel, 2014; Ristow and Schmeisser, 2014). Similarly, it was shown recently that ROS production arising from perturbed ER redox homeostasis leads to a protective response that increases lifespan (Hourihan et al, 2016). In each of these examples, mutants that lack the capacity to detoxify ROS (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…RNAi-mediated memo-1 knockdown caused a significant increase in nuclear SKN-1::GFP (Figure 2C and D). Under oxidative stress conditions, SKN-1 phosphorylation/activation is mediated by p38 mitogen-activated protein kinase (MAPK; [Inoue et al, 2005]), which is phosphorylated and activated by SEK-1/MAPKK (Inoue et al, 2005; Hourihan et al, 2016). Importantly, reducing memo-1 function either by RNAi or mutation resulted in higher levels of phospho-p38 MAPK (Figure 2E and F), and loss of sek-1 completely abolished memo-1(-) mediated-longevity (Figure 2G).…”
Section: Resultsmentioning
confidence: 99%
“…However, very high concentrations of metformin (5 m m ) were required to observe significant inhibition of mitochondrion respiratory chain complex 1 activity (He & Wondisford, 2015). Recent studies showed that Nrf2 can be activated by the ER unfolded protein response sensors IRE1α (Hourihan, Moronetti Mazzeo, Fernandez‐Cardenas, & Blackwell, 2016) and PERK (Cullinan et al., 2003). However, in our hands, PERK activation was not detected when HDFs were treated with 100 μ m metformin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in C. elegans and human cells, new evidence suggests that cysteine sulfenylation of IRE1 kinase at its activation loop inhibits IRE1-mediated UPR and initiates a p38 antioxidant response driven by NRF2. The data suggest that IRE1 has an ancient function as a cytoplasmic sentinel that activates p38 and NRF2 [50].…”
Section: Nrf2 Participates In the Unfolded Protein Response (Upr)mentioning
confidence: 89%